INDUSTRI PARIWISATA DI KOTA JAMBI 2006 – 2020 - Yuda Ardika, Tri; Azmi, Ulul; Heidi Karmela, Siti (Universitas Batanghari Jambi, 2025)
The problem in this research concerns the tourism industry in the tourist area in Jambi City. The aim of this research refers to the problems raised, so the aim is to explain that tourism destinations can influence the tourism industry in Jambi City and describe how tourism contributes to the economy of communities around tourist destinations in Jambi City. The method used in this research is a historical research method which consists of several stages, namely heuristics, criticism, interpretation and historiography. The primary source used in this research is interviews with traders in tourist destination areas in Jambi City. Meanwhile, secondary sources used are books and internet sources. The research results provide an explanation of how the activities of Tourism Industry traders generate a lot of profits during the holiday season. The results of this research also provide an explanation of the economic life around the tourist destination area in Jambi City. The conclusion of this research is the Tourism Industry in Jambi City 2006 -2020. Experiencing many significant changes in several sectors, one of which is the Gentala Arasy Bridge, where more and more visitors are coming to this tourist attraction to enjoy the Batanghari River, especially now that they can easily get to Jambi, Sebrang City.